Queering up the mother with Michel Tremblay and Xavier Dolan. Issue 3 (January 2018) - Bourdeau, Loïc
Abstract : Although five decades separate Michel Tremblay (1942) and Xavier Dolan (1989), their artistic productions – writing and filmmaking – demonstrate striking resemblances in their content, objectives, and critical reception. Since J'ai tué ma mère in 2009, many commentators have underscored a mirror effect between the two in relation to their treatment of women and sexuality. The following contribution investigates, more specifically, the notion of motherhood in Tremblay's autobiographical triptych ( Les vues animées [1990], Douze coups de théâtre [1992], Un ange cornu avec des ailes de tôles [1994]) and Dolan's love saga ( J'ai tué ma mère [2009], Les amours imaginaires [2010], and Laurence anyways [2012]) to shed light on strategies of representation and maternal emancipation. Looking at questions of performance, screams, as well as distance and absence, each author offers new, less restrictive conceptions of motherhood, along with new forms of kinship, and above all, broader comments on the contexts in which their works were produced. Tremblay represents the primal scene of disrupted Quebecois motherhood and a lens through which to analyze Dolan's more recent films; films that denounce the burden of contemporary anxieties and persisting forms of oppression.